Case report: Spindle cell neoplasm presenting as a spontaneous intestinal perforation in a term infant - Callaghan, Lauren T.; Lafreniere, Anthea; Onwuka, Ekene A.; Beckman, Ross M.; Foster, Jennifer H.; Quintanilla, Norma; Guillory, Charleta; Lee, Timothy C.; Cheng, Lily S. (Frontiers in Pediatrics, 2022)
Spontaneous intestinal perforations in the neonatal population are mostly associated with low birth weight, prematurity, and necrotizing enterocolitis. Spontaneous intestinal perforation in the absence of these risk factors is extremely rare and should raise clinical concern for an underlying bowel pathology. Here we present a unique case of a normal-weight, full-term girl with spontaneous intestinal perforation due to a spindle cell neoplasm with a novel BRAF mutation and infantile fibrosarcoma-like morphology. Though rare, malignancy should be considered in the differential diagnosis for bowel perforation in an otherwise healthy, term infant as complete surgical excision can be curative.